2011
DOI: 10.1038/nbt.1914
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing across a prostate cancer cohort identifies PCAT-1, an unannotated lincRNA implicated in disease progression

Abstract: High-throughput sequencing of polyA+ RNA (RNA-Seq) in human cancer shows remarkable potential to identify both novel markers of disease and uncharacterized aspects of tumor biology, particularly non-coding RNA (ncRNA) species. We employed RNA-Seq on a cohort of 102 prostate tissues and cells lines and performed ab initio transcriptome assembly to discover unannotated ncRNAs. We nominated 121 such Prostate Cancer Associated Transcripts (PCATs) with cancer-specific expression patterns. Among these, we characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
868
3
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 949 publications
(901 citation statements)
references
References 47 publications
21
868
3
9
Order By: Relevance
“…Emerging studies suggest that lncRNAs are involved in the progression of PCa. PCAT‐1, transcribed from the introns of known genes which correlate with the differentiation degree of PCa, was identified as a prostate‐specific regulator of cell proliferation 15. Prostate cancer antigen 3 (PCA3), also known as differential display 3 (DD3), has been thoroughly explored as a PCa‐specific biomarker 16.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging studies suggest that lncRNAs are involved in the progression of PCa. PCAT‐1, transcribed from the introns of known genes which correlate with the differentiation degree of PCa, was identified as a prostate‐specific regulator of cell proliferation 15. Prostate cancer antigen 3 (PCA3), also known as differential display 3 (DD3), has been thoroughly explored as a PCa‐specific biomarker 16.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence indicates that LncRNAs which are RNA specis >200 bp in length (9) and frequently polyadenylated (10), are involved in physiological aspects of cell-type determination and tissue homeostasis (11), and in cancer lncRNAs are known to play important roles in carcinogenesis and tumor progression (12)(13)(14)(15)(16). One of the overexpressed lncRNAs in prostate cancer, PCGEM1, is tissue specific and PCa-associated lncRNA gene (15), whereas another highly expressed lncRNA, PRNCR1 (PCAT8), is pervasively transcribed from the critical region of 8q24 Region 2, which is significantly associated with PCa susceptibility (17).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also demonstrated that a novel long non-coding RNA (named PlncRNA-1) was frequently overexpressed in PCa cell lines and tissues and associated with cell viability and cell apoptosis (18). Recent studies have revealed the contribution of other lncRNAs as proto-oncogenes, drivers of metastatic transformation and tumor suppressor genes in prostate cancer, such as prostate cancer gene 3 (PCA3), metastasis associated in lung adenocarcinoma transcript 1 (MALAT-1), and PCAT-1 (13,(19)(20)(21). However, the global expression profile of lncRNAs in androgen-dependent (AD) to androgen-independent (AI) prostate cancer is not fully uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…The HOTAIR ncRNA was the prototype lincRNA in humans and was shown to have a role in regulating repressive chromatin at the HOXD gene cluster and in modulating the cancer epigenome, 17,18 however this function may not be conserved in mice. 19 Many thousands of lincRNAs have now been identified, [20][21][22][23][24][25] that mostly appear to cis-acting silencer, i.e., the macro lncRNA, on the maternal allele. The Airn macro lncRNA silences the Igf2r imprinted gene cluster.…”
Section: How Can Non-coding Rnas Function In Gene Regulation?mentioning
confidence: 99%
“…The approach of ab initio reconstruction of the transcriptome based on identifying transcription islands and connecting them by split-mapped reads, has allowed the detection of many thousands of novel spliced lncRNAs. 22,25,67 Bioinformatic pipelines have been developed including programs such as Scripture, 22 Cufflinks 78 and the split-mapper TopHat, 79 which greatly increased the numbers and reliability of detected lncRNAs. The spliced nature of lncRNAs thus increases confidence in identifying novel transcripts but a bioinformatic pipeline to detect macro lncRNAs in RNA-seq data are lacking.…”
Section: The Unusual Transcript Biology Of Macro Lncrnasmentioning
confidence: 99%